A bibliometric analysis on the progress of myocardial bridge from 1980 to 2022 - Chen, Liang; Yu, Wen-Yuan; Liu, Rui; Gao, Ming-Xin; Wang, Bo-Lin; Ding, Xiao-Hang; Yu, Yang (Frontiers in Cardiovascular Medicine, 2023)
The vast majority of patients with myocardial bridge (MB) are asymptomatic, but this anomaly may be associated with myocardial stable or unstable angina, vasospastic angina, acute coronary syndrome, malignant arrhythmias and sudden cardiac death. By retrieving the relevant literature of MB from January 1, 1980 to July 31, 2022, qualitative and quantitative evaluations are carried out to visualize the scientific achievements in this field. The data were from the Web of Science Core Collection database. The bibliometric tools – CiteSpace, VOS viewer and alluvial generator were used to understand the development of disciplines and research hotspots in this field. A total of 630 MB-related articles were collected by Web of Science Core Collection database from 1980 to July 2022, and the number of published papers and citations were in a fluctuating growth trend. United States of America was the leading country, Stanford University was the leading institution, and Jennifer A. Tremmel was the most productive researcher in this field. According to co-citation analysis, burst detection and alluvial flow map, the prevalence and prognosis, mechanism atherosclerosis, hemodynamic significance, and molecular autopsy have become more and more popular recently. However, further research and collaboration are still required worldwide. Our findings can help researchers grasp the research status of MB and determine new directions for future researches as soon as possible.